THE MECHANISM FOR PROMOTING PRODUCTS AND SERVICES TO THE EXTERNAL MARKET - Tamila Musredinova (International Scientific and Current Research Conferences, 2021)
the thesis highlights the initial plan of action. In modern conditions, each enterprise plans to bring its product to the foreign market, that is, to engage in export. But desire alone is not enough for this, because export is a labor-intensive process that requires high costs. It is important to have a clear plan of action and regularly study new strategy methods for entering foreign markets and, of course, take into account what problems the company will face when entering foreign markets.